Prognostic potential of protein glycovariants for head and neck cancer therapy - Salminen, Sadie (My University, 2023)
Over 900 000 new head and neck cancer cases are diagnosed annually. Presently, head and neck cancers lack specific diagnostic, prognostic, and predictive biomarkers for targeted treatments. Glycosylation is a crucial post-translational step as it modifies and determines stability, composition and function of lipids and proteins. In this study, integrin-lectin nanoparticle immunoassay was used to analyse aberrant glycosylation of integrins. Integrins are transmembrane receptor proteins involved in cell and extracellular matrix communications and cell adhesion. Integrins are linked to cancer traits such as metastasis and evasiveness. Integrin-recognizing monoclonal antibodies (Mabs) (ITGA2, ITGA3, ITGA5, ITGA6, ITGB4, ITGB1) and lectin-conjugated Europium(III´)-nanoparticles (ConA, AAL, UEA, MAA, SBA, WFL) were used as captures and tracers, respectively, to analyse tissue samples from head and neck squamous cell carcinoma patients (n = 21). The results were examined for integrin-lectin combinations that had prognostic potential in diagnosing nodal positivity, locoregional recurrence and distant metastasis. With the integrin-lectin combinations, higher signals were observed in the tumour sample than the adjacent healthy samples, indicating that the observed glycosylation of integrins could be a cancer-linked abnormality. For neck nodal positivity at diagnosis, a significantly lower expression of the combination ITGB4 + WFL were observed in nodal positive tumours (p=0.032; AUROC=0.18; 95% CI: 0.00 to 0.41, p=0.021). For recurrence prognostication, a significantly lower ITGB4 + ConA expression was observed in locoregional recurrence (p=0.032; AUROC=0.150; 95% CI :0.00 to 0.344, p=0.021). For distant metastasis significantly lower ITGB4 + UEA expression was observed (p=0.007; AUROC= 0.907; 95% CI: 0.760 to 1.000, p=0.027). The positive findings of this study should be validated in larger patient cohorts.